The Subject Of Study Of The Political Economy, An Eclectic Approach - Arihir ,Mustapha (جامعة الوادي University of Eloued, 2025)
There are many opposing viewpoints regarding what the subject of the political economy should be. Many academicsand researchers havestudied thistopic; certain authors highlighted "wealth"as thefoundation for the economic issue, some have emphasized “scarcity”, others focus on “production” as a topic of study, and others insist on “exchanges”. We approach these conflicting approaches by applying the idea of “eclecticism,” which consists of choosing the most appropriate from each one.
مقال
Keywords: Economics 1; Subject of study 2; Eclictism 3; Political economy 4; Epistemology 5.